Penerapan Metode Kooperatif Model Group Investigation Sebagai Alternatif dapat Meningkatkan Prestasi Belajar Tematik Tentang Peristiwa dalam Kehidupan Siswa Kelas VI SD - Hasnawati Rasyid (Universtas Negeri Makassar, 2022)
The purpose of this study was to find out how far the understanding and mastery of thematic subjects about events in life after the implementation of the GI cooperative learning model for Class VI UPT SD Inpres Juppai students. The research method used is this research is action research (action research), because research is conducted to solve learning problems in the classroom. The conclusion of the research is that cooperative learning of the GI model has a positive impact on improving student achievement as indicated by an increase in student learning completeness in each cycle, namely cycle I (66.67%) with a percentage of completeness of 22.22% learning completeness cycle II (79.72 %) with a completeness percentage of 87.73%, and cycle III (88.61%) with a completeness percentage of 91.25%.